2008, No.3, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2019)
Jonas Mackevičius, The regulation of financial accounting in Lithuania during the Soviet occupation (1966–1989) , 7 Vita Daubarienė, Kristina Rudžionienė, The selection of evaluation methods representing true and fair view of a financial performance of a company, 18 Darius Gliaubicas, The research of management accounting methods in Lithuanian companies, 32 Romualdas Valkauskas, Economic fluctuations: indicators, statistical description, 52 Vladislav Tomaševič, The main principles of policy formation of working capital management, 61 Martynas Novikovas, Application of Berry ratio in transfer pricing, 74 Romualdas Bartaška, Liuda Gargasienė, External and internal audit of projects financed by EU funds, 81 Agnė Ramanauskaitė, Exposure of intellectual capital in financial report of a company, 94